2022
DOI: 10.3168/jds.2022-21777
|View full text |Cite
|
Sign up to set email alerts
|

Models to predict milk fat concentration and yield of lactating dairy cows: A meta-analysis

Abstract: Few models have attempted to predict total milk fat because of its high variation among and within herds. The objective of this meta-analysis was to develop models to predict milk fat concentration and yield of lactating dairy cows. Data from 158 studies consisting of 658 treatments from 2,843 animals were used. Data from several feed databases were used to calculate dietary nutrients when dietary nutrient composition was not reported. Digested intake (DI, g/d) of each fatty acid (FA;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Surprisingly, the milk fat content observed in our study (35.5 g/kg) was higher than that of the other reports (mean 32.0 g/kg) conducted in different years on the same farms, in 4 th calving cows, with BW and days in milk similar to those of the presents study (Salvador-Loreto et al, 2016;Salas-Reyes et al, 2019;Esparza-Jiménez et al, 2020) and from other farms in the same region reported by Morales et al (2011 ) of 26.7 (g/kg). Although the milk fat content values mentioned here are in the normal range reported in the literature (Daley et al, 2022).…”
Section: Discussionsupporting
confidence: 49%
“…Surprisingly, the milk fat content observed in our study (35.5 g/kg) was higher than that of the other reports (mean 32.0 g/kg) conducted in different years on the same farms, in 4 th calving cows, with BW and days in milk similar to those of the presents study (Salvador-Loreto et al, 2016;Salas-Reyes et al, 2019;Esparza-Jiménez et al, 2020) and from other farms in the same region reported by Morales et al (2011 ) of 26.7 (g/kg). Although the milk fat content values mentioned here are in the normal range reported in the literature (Daley et al, 2022).…”
Section: Discussionsupporting
confidence: 49%
“…Maxin et al [ 35 ] demonstrated the accuracy and precision of short-chain and long-chain FA as predictors of milk fat production, although their models were based on in vitro studies. In a recent study, Daley et al [ 36 ] identified C16:0, C18:2, and C18:3 as predictors of milk fat production. These findings, combined with the present study, emphasize the significance of considering the FA profile of the diet as predictive variables of both milk fat production and proportion.…”
Section: Discussionmentioning
confidence: 99%
“…In the eighth revised edition of Nutrient Requirements of Dairy Cattle, the National Academies of Sciences, Engineering, and Medicine ( NASEM ) proposed an equation to predict milk fat yield ( MFY ) using animal characteristics and diet composition as input variables ( NASEM, 2021 ). This multivariate equation was developed and cross-validated by Daley and Hanigan (2019) and Daley et al (2022) and reads as follows: Milk_Fat_g = 453 − (1.42 × An_LactDay ) + [24.52 × ( Dt_DMIn − Dt_FAIn )] + (0.41 × Dt_DigC160In × 1,000) + (1.80 × Dt_DigC183In × 1,000) + (1.45 × Abs_Ile_g ) + (1.34 × Abs_Met_g ), where Milk_Fat_g = MFY (g/d), An_LactDay = DIM (d), Dt_DMIn = DMI (kg/d), Dt_FAIn = FA intake (kg/d), Dt_DigC160In = predicted digested 16:0 intake (kg/d), Dt_DigC183In = predicted digested 18:3 intake (kg/d), Abs_Ile_g = absorbed Ile (g/d), and Abs_Met_g = absorbed Met (g/d).…”
mentioning
confidence: 99%
“…The issued NASEM model has been developed and cross-validated using data from the scientific literature ( Daley et al, 2022 ). Measurements were performed under controlled conditions, and actual DMI was available.…”
mentioning
confidence: 99%